Human Security Paradox: Between Human Welfare and the Threat of Environmental Damage - Anggayudha, Zaihan Harmaen; Rafsanjani, Jody Imam (Jurnal Cakrawala Hukum, 2024)
Human security serves as a link between the concept of security and human rights (HAM), and it is considered to overcome the weaknesses of the traditional security concept. The concept makes humanitarian issues into a security domain, such as food, health, economic, environmental, personal, community, and politics, to ensure everyone is prosperous and free from threats and fear. As if it were a paradox, Human Security also takes environmental issues into account. Economic activity is not infrequently one of the causes of environmental damage. This article aims to determine the threat of environmental damage due to economic activity from a Human Security perspective and its paradoxes. Using qualitative methods through a security study approach, human rights, and environmental law were carried out through desk research and then analyzed with analytical description. Poverty is one of the discussions of Human Security. In Indonesia, a decent life is a fundamental right of every citizen protected by the constitution. When economic activity impacts the environment and threatens the environment and humans, this problem becomes a security challenge. The state becomes an important actor and is responsible for providing solutions and has a strategy to substitute these livelihoods with values ​​that are at least almost the same or even exceed them so that in the end, the state is not only an institution that can only issue prohibition instruments but is also able to present solution instruments.